Neurodevelopmental outcome following prenatal diagnosis of a short corpus callosum. (26th April 2019) - Meidan, Roni; Bar‐Yosef, Omer; Ashkenazi, Itay; Yahal, Orr; Berkenstadt, Michal; Hoffman, Chen; Tsur, Abraham; Achiron, Reuven; Katorza, Eldad
Abstract: Objective: Data regarding the neurodevelopmental outcome of fetal short corpus callosum (CC) diagnosed according to standard reference charts is scarce. The purpose of this study was to assess whether the finding is related to neurodevelopmental delay, and to examine reclassification to normal fetal CC length using CC length/EFW ratio. Method: Historical prospective cohort study including pregnant women who were referred for fetal neurosonogram due to abnormal CC. Short CC was defined below the 5 th percentile according to reference charts. Twenty cases were included in the study group and compared with a control group of 59 normal cases. The patients in the study group were divided into two groups according to CC length/EFW ratio. Children's neurodevelopment was assessed using the Vineland Adaptive Behavior Scale (VABS). Results: VABS scores were within normal range in 90% of the cases. There was no significant statistical difference between the study group and the control group. In addition, there was no statistically significant difference between fetuses reclassified as normal callosal length according to CC length/EFW ratio in comparison to the control group. Conclusion: The neurodevelopmental outcome of fetuses with diagnosed short CC did not differ from the neurodevelopment of normal fetuses in the control group. Abstract : What's already known about this topic? Callosal anomalies prognosis is controversial. It may be associated with neurodevelopmental delay and is apparently worse if additional anomalies are present. Data regarding neurodevelopmental outcome is scarce, and its significance is not well established. What does this study add? The study's main objective was to determine whether diagnosed fetal short CC according to standard reference charts influences neurodevelopment. Moreover, to assess if reclassification of the fetuses according to CC length/EFW ratio affects neurodevelopmental outcome.